Policy Evaluation and Economic Policy Advice - Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Arguably, one of the most important developments in the field of applied economics during the last decades has been the emergence of systematic policy evaluation, with its distinct focus on the establishment of causality.By contrast to the natural sciences, the objects of our scientific interest typically exert some influence on their treatment status under the policy to be evaluated and on their economic outcomes. Thus, economic policy advice can only be successful, if it is based on an appropriate study design, experimental or observational. It will strive in societies that provide liberal access to data, accept the merits of randomized assignment and guard the independence of research institutions.
Keywords: A11; C01; H50; 330; Policy evaluation; applied economics; causality; policy advice; Wirtschaftspolitische Beratung; Wirtschaftspolitische Wirkungsanalyse; Wirtschaftsforschung; Kausalanalyse; Deutschland